1994
DOI: 10.1007/bf01533366
|View full text |Cite
|
Sign up to set email alerts
|

T helper cell dysfunction in systemic lupus erythematosus (SLE): Relation to disease activity

Abstract: Patients with systemic lupus erythematosus (SLE) are known to have defects in both humoral and cellular immunity. The significance of defective T cell-mediated immunity and its relationship to disease activity have not been clearly established. We studied in vitro T helper cell (Th) function in 150 SLE outpatients and correlated Th function with validated measures of disease activity. Interleukin 2 (IL-2) production by peripheral blood mononuclear cells (PBMC) was measured after stimulation with the recall ant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
37
0
10

Year Published

1995
1995
2009
2009

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 80 publications
(52 citation statements)
references
References 23 publications
1
37
0
10
Order By: Relevance
“…A diminished T helper cell response to influenza in patients with SLE, as measured by IL-2 secretion in the supernatant of the influenza-stimulated PBMCs of nonvaccinated patients, has been reported previously (10). We observed a decreased CD8ϩ T cell recall response to influenza antigens in patients with SLE, which is in accordance with results of a previous study (11).…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…A diminished T helper cell response to influenza in patients with SLE, as measured by IL-2 secretion in the supernatant of the influenza-stimulated PBMCs of nonvaccinated patients, has been reported previously (10). We observed a decreased CD8ϩ T cell recall response to influenza antigens in patients with SLE, which is in accordance with results of a previous study (11).…”
Section: Discussionsupporting
confidence: 92%
“…Previous studies demonstrated a normal capacity of PBMCs from patients with SLE to respond to different stimuli, although diminished cellmediated responses may be present during active disease (10,(24)(25)(26). Because our cohort of patients with SLE had predominantly quiescent disease, this may explain their normal responses to SEB.…”
Section: Discussionmentioning
confidence: 76%
See 1 more Smart Citation
“…In other systems, downregulation of responsiveness to recall antigens is associated with a decrease in T helper-1 type cytokines (10,17,21). In healthy pregnant women, PBMC have diminished IL-2 production after stimulation with recall antigens (11).…”
Section: Discussionmentioning
confidence: 99%
“…Although the cause of this is unknown, it is thought that disease flares represent times of greatest immune dysfunction (35). To investigate whether changes in the level of immune dysfunction could affect the regulation of EBV infection, the frequency of virally infected cells was studied in patients with active and inactive disease.…”
Section: Sle Disease Activity Affects the Frequency Of Virally Infectmentioning
confidence: 99%